INITIALISMS IN GEN Z TWITTER (X): A QUALITATIVE ANALYSIS OF MORPHOLOGICAL PATTERNS AND COMMUNICATIVE FUNCTIONS - Silvia Utami; Tengku Nindy Ananda Putri; Dita Indah Sari; Assyifa Queen `Zahabya (Acceleration: Multidisciplinary Research Journal, 2025)
This study investigates how Generation Z constructs and uses initialisms in Twitter (X), focusing on their morphological patterns and communicative functions. While previous studies have highlighted the social meanings of abbreviations in digital discourse, limited attention has been given to the systematic morphological structures underlying initialism formation and their functional roles within a single platform-specific context. Using a qualitative descriptive design, the data were collected through purposive sampling of publicly accessible Gen Z tweets posted between October and December 2025. Screenshots of posts containing initialisms were documented and analyzed using content analysis. The findings reveal 85 distinct initialisms, classified into Non-Elliptical (68 forms), Elliptical (12 forms), and Non-Alphabetic (6 forms). Non-elliptical forms dominate, reflecting Gen Z’s reliance on fully abbreviated, letter-by-letter constructions that support rapid processing and platform efficiency. Across all categories, initialisms serve key communicative functions, operating as pragmatic tools for stance-taking, emotional signaling, identity construction, boundary marking, and interaction management that strengthen in-group belonging and facilitate high-speed digital interaction. This study contributes to contemporary discussions on digital morphology and Gen Z sociolinguistics by showing how compressed linguistic forms evolve in response to platform constraints and social dynamics. The implications highlight the need to recognize initialisms as a central component of emerging internet-mediated language change.